The variability of field emissions is critical to assessing the environmental impacts of vegetables: A Benin case-study. (1st June 2017) - Perrin, Aurélie; Basset-Mens, Claudine; Huat, Joël; Gabrielle, Benoit
Abstract: The development of urban farming provides potentially powerful leverage for the sustainable development of cities in developing countries in general, and in Africa in particular. However, the associated potential impacts on the environment need to be evaluated using a recognized assessment methodology such as Life Cycle Assessment (LCA). Here, we set out to produce such references for tomatoes grown in urban gardens in Benin, and to examine how their impacts were affected by the variability of field emissions of reactive nitrogen, responsible for a major share of non-toxic impacts. A stratified sample of 12 fields was surveyed and used to design a representative mean for urban tomato gardens in Benin. To analyze the sensitivity of environmental impacts to management practices and environmental conditions, yields and nitrogen emissions from extreme scenarios were simulated with the crop model STICS. Overall, the environmental impacts of urban garden tomatoes in Benin were 4–23-fold greater than the impacts of tomatoes grown in European cropping systems, due to low and variable crop yields, high fuel consumption for irrigation, large emissions of nutrients and an excessive use of insecticides. For extreme scenarios, impacts were up to 3-fold greater than the impact of the representative mean as a result of complex biophysical mechanisms involved in nitrogen emissions. We concluded that parameters relative to irrigation (total rate and application frequency) and soil properties (pH, water holding capacity) should be included in the estimation of nitrogen emissions for LCA of vegetables. To reduce the impacts of urban garden systems, we recommend reducing fertilization to better fit to nutrient requirements with regard to potential yields, and avoiding a systematic use of insecticides. Highlights: Global warming potential of urban garden tomato is 10 times higher than the impact of European tomato under cold greenhouse. High ecotoxicity potential results from excessive use of cypermethrin, an active substance against insects Excessive nitrogen rates may increase eutrophication and climate change potentials 3-fold without noticeable yield gain Nitrogen inputs from soil mineralization leads to significant nitrogen emissions even for extensive nitrogen management.